Determinan Pengangguran: Apakah SMK Berpengaruh terhadap Pengangguran? - Baiq Amiatun Hidayah; Luluk Fadliyanti; Rishan Adha (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
This study aims to analyze the effect of economic growth, investment, the ratio of the number of students and vocational schools on unemployment in West Nusa Tenggara Province. This study uses Eviews 12 to obtain research results. The data method of this study is quantitative with secondary data obtained from the Central Statistics Agency. The research data used is panel data for 2013-2022. The analysis model used is multiple linear regression and the best model used is the Fixed Effect Model after going through the chow test and hausman test. The results of the research obtained in this study are that the economic growth variable has a positive and significant effect on unemployment in West Nusa Tenggara Province, the effect of the investment variable on the unemployment rate is negative but the significance level of investment is very high so that it is not significant for unemployment in West Nusa Tenggara Province, and the ratio of the number of students and the number of vocational schools is positive but not significant for unemployment in West Nusa Tenggara Province. The conclusion in this study is that overall the variables have a simultaneous effect on the variables.   Keywords: Economic Growth, Investment, Ratio Of The Number Of Students And The Number Of Vocational Schools, Unemployment.